Taeniid species of the Iberian wolf (Canis lupus signatus) in Portugal with special focus on Echinococcus spp. - Guerra, Diogo; Armua-Fernandez, Maria Teresa; Silva, Marta; Bravo, Inês; Santos, Nuno; Deplazes, Peter; Carvalho, Luís Manuel Madeira de (International Journal for Parasitology: Parasites and Wildlife, 2014)
Articles in International Journals Taeniid species represent relevant pathogens in human and animals, circulating between carnivorous definitive hosts and a variety of mammalian intermediate hosts. In Portugal, however, little is known about their occurrence and life cycles, especially in wild hosts. An epidemiological survey was conducted to clarify the role of the Iberian wolf as a definitive host for taeniid species, including Echinococcus spp. Wolf fecal samples (n = 68) were collected from two regions in Northern Portugal. Taeniid eggs were isolated through a sieving-flotation technique, and species identification was performed using multiplex- PCR followed by sequencing of the amplicons. Taenia hydatigena (in 11.8% of the samples), Taenia serialis (5.9%), Taenia pisiformis (2.9%), Taenia polyacantha (1.5%) and Echinococcus intermedius (Echinococcus granulosus ‘pig strain’, G7) (1.5%) were detected. This is the first study to characterize the taeniid species infecting the Portuguese Iberian wolf, with the first records of T. polyacantha and E. intermedius in this species in the Iberian Peninsula. Iberian wolves can be regarded as relevant hosts for the maintenance of the wild and synanthropic cycles of taeniids in Portugal.